The Russian necropolis in Japan: problems and prospects for studying - E. I. Krasilnikova; S. S. Paichadze (Омский научный вестник: Серия "Общество. История. Современность")
The paper is devoted to a historiographical review of the literature dedicated to the study of the history of the Russian necropolis in Japan and the prospects for further research on this topic. The external conditions of increasing interest in the topic of the history of the Russian necropolis abroad are characterized. The definition of the historical necropolis is given. The review is structured according to the chronological principle. The main studies of Japanese and Russian historians are revealed. The authors identified the primary studies in Russian and Japanese and concluded that is not much research on the history of the Russian necropolis in Japan until the end of the twentieth century, but the relevance of this topic in the past three decades. The paper shows the predominant exhaustion of the subject within the framework of traditional necropolistics. The paper proposes possible options for further study of the history of the Russian necropolis in Japan within discipline Memory studies and also with the use of cultural anthropology, social history and political sciences approaches.